EFEKTIVITAS LKPD SAINS BERORIENTASI MODEL PEMBELAJARAN BERBASIS MASALAH DALAM MENUMBUHKAN KECAKAPAN BERPIKIR KREATIF - Pusfarini, Pusfarini; abdurrahman, abdurrahman; Jalmo, Tri (Jurnal Pendidikan Progresif, 2016)
TheEffectiveness of Problem Based Learning’s Worksheet (LKPD)- Oriented forEnhancing Students Creative Thinking. This study aimed to describe the impact of the use of Worksheet Students (LKPD) oriented model of Problem Based Learning (PBL) on theScience topicsabout Sense of Hearing and Sonar Systems in Human Beings. The data collection is done with quantitative approach using a quasi-experimental design with Nonequivalent pre-test post-test. A total of 74 students of a junior high school in the city of Bandar Lampung involved as research samples. Samples were divided into two groups: an experimental group where students acquire learning using LKPD-based treatment and control groups use traditional PBL LKPD in students’ books. The results showed that LKPD based on PBL effective in use for science topics of Sense of Hearing and Sonar Systems in Beings with high levels of effectiveness (N-Gain = 0.78). Keywords: LKPD, PBL, creative thinking skill, sense of hearing and sonar systems in human beings DOI: http://dx.doi.org/10.23960/jpp.v6.i1.201601